Psychiatric Agencies in Brazil: Psychiatric Reform and the Psychotropic Epidemic - Kimati Dias, Marcelo; Muhl, Camila (Argumentum, 2020)
This article presents a sociohistorical analysis of mental health policies in Brazil, by means of examining two distinct movements: the links and development of Brazilian Psychiatric Reform and the expansion of a psychiatric practice strongly connected to the pharmaceutical industry. Firstly, it describes the evolution of these two movements, based on the framework of historical sociology. Secondly, it presents the analysis of data based on the Theory of Structuration by Anthony Giddens, which shows how the expansion of the use of psychotropics has developed within the structures and services created under Psychiatric Reform policies, in a process of coexistence. Brazilian Psychiatric Reform has not opposed the development of an epidemic of the use of psychiatric medication.